2020
DOI: 10.1111/dgd.12667
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory synaptic transmission tuned by Ca2+ and glutamate through the control of GABAAR lateral diffusion dynamics

Abstract: The GABAergic synapses, a primary inhibitory synapse in the mammalian brain, is important for the normal development of brain circuits, and for the regulation of the excitation‐inhibition balance critical for brain function from the developmental stage throughout life. However, the molecular mechanism underlying the formation, maintenance, and modulation of GABAergic synapses is less understood compared to that of excitatory synapses. Quantum dot‐single particle tracking (QD‐SPT), a super‐resolution imaging te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…While this observation indicates that an influx of extracellular Ca 2+ may underlie the alterations observed in GABA A R dynamics, it did, so far, not exclude that release from the internal stores may contribute to the increase in cytoplasmic Ca 2+ concentration. This question is of relevance since it has been shown that cytoplasmatic Ca 2+ can have different effects on synaptic regulation depending on where it comes from [ 6 ]. While Ca 2+ release from the endoplasmic reticulum (ER) suppressed GABA A R lateral diffusion [ 8 ], Ca 2+ influx through the plasma membrane leads to an increase in their lateral diffusion [ 8 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this observation indicates that an influx of extracellular Ca 2+ may underlie the alterations observed in GABA A R dynamics, it did, so far, not exclude that release from the internal stores may contribute to the increase in cytoplasmic Ca 2+ concentration. This question is of relevance since it has been shown that cytoplasmatic Ca 2+ can have different effects on synaptic regulation depending on where it comes from [ 6 ]. While Ca 2+ release from the endoplasmic reticulum (ER) suppressed GABA A R lateral diffusion [ 8 ], Ca 2+ influx through the plasma membrane leads to an increase in their lateral diffusion [ 8 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the strength of inhibitory synaptic transmission depends on the number of gamma-aminobutyric acid receptors (GABA A Rs) present at synapses [ 5 ]. The synaptic localization of GABA A Rs is, in turn determined both by their clustering via synaptic scaffold proteins as well as by the control of their lateral diffusion through changes in the intracellular Ca 2+ concentration [ 6 ]. Indeed, the number of GABA A Rs accumulating at the synapse has been shown to depend on the release of Ca 2+ from the internal stores via activation of the IP3R1 and PKC [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that the Gaba receptor is involved in the regulation of the differentiation of rodent neural progenitor cells [18]. The Gaba receptor is a G-protein-coupled receptor that is associated with inositol 1,4,5-triphosphate (IP3)-induced Ca 2+ signals [20,21,22]. We hypothesized that the Gaba-receptor-mediated Ca 2+ signals are involved in Jdp2-regulated neural differentiation.…”
Section: Enhancement Of Ca 2+ Signals In Jdp2 Ko Gabra6 + Gcpsmentioning
confidence: 99%
“…19 e190024_2 cells with high sensitivity, leading to an understanding of the mechanisms of pathology. Dr. Hiroko Bannai (Waseda University) will talk about the current status, problems, and potential of single-molecule imaging studies in neurological disease research [8,9].…”
mentioning
confidence: 99%
“…In recent years, single-molecule imaging plays an important role that contributes to the detection of abnormalities in disease model cells with high sensitivity, leading to an understanding of the mechanisms of pathology. Dr. Hiroko Bannai (Waseda University) will talk about the current status, problems, and potential of single-molecule imaging studies in neurological disease research [ 8 , 9 ].…”
mentioning
confidence: 99%